Constant disturbance in critical care units influenced patients’ sleep quality - Zainah Mohamed; Gurbinder Kaur Jit Singh; Aishairma Aris; Nur Aishah Awang Maharum; Lalitha Velayom (Penerbit Universiti Kebangsaan Malaysia, 2020)
The critically ill patients’ experiences and sleep quality are a crucial aspect of quality care in the critical care setting. The aim of this study was to identify the perceived sleep quality and patients’ experiences during their stay in critical care units. Data was collected using validated and reliable self-reported questionnaires by patients on sleep quality in the intensive care unit and intensive care experience (ICEQ) for two months’ duration. A random sampling was used in participants’ selection and 55 patients who fulfilled the inclusion criteria participated in this study. Descriptive and Inferential analyses were used in data analysis. Mean age of the respondents was 52 with 64% male. More than half (58.2%) patients reported poor sleep quality while in critical care units. Disruption in patients’ sleep was mainly due to noises from medical devices alarms (76.36%) and constantly taking vital signs e.g. measuring blood pressure (70.90%). Even though more than half of the patients (54.5%) reported more frightening experiences while in critical care units, but overall their experience was either positive or neutral. Patients (16.36%) who stayed longer in critical care units between 8 -12 days reported better sleep quality. Reducing noise by minimizing the alarm sounds and attend to any alarm as soon as possible may help to promote better outcome for patients’ sleep quality and experience while in critical care. It is important for nurses to plan and cluster the patient’s care to avoid constant disturbance.